Productivity and Profitability of Mung bean (Vigna radiata L.) as Influenced by Foliar Application of Nutrients under Hot Arid Conditions of Rajasthan: SHORT COMMUNICATION - Bajiya, Rohitash Bajiya; Hansa Lakhran; Moola Ram; Shiv Singh Meena (Annals of Arid Zone, 2025)
A field experiment was conducted at Agricultural Research Sub-Station, Nagaur, Agriculture University, Jodhpur during (kharif) 2022 to explore the effect of foliar application of nutrients to enhance growth, yield and productivity and also combating the dry spell effect during flower initiation and pod formation stage in mung bean. The elven treatments, viz, absolute control (without foliar application); foliar spray of nitrogen urea @ 1% at flowering initiation stage (FI); foliar spray of nitrogen urea @ 1% at FI and Pod formation (PF) stage; foliar spray soluble NPK (19:19:19) @ 1% at FI stage; FS soluble NPK (19:19:19) @ 1% at FI and  (PF) stage; foliar spray of soluble KNO3 @ 0.5% at FI stage; foliar spray of soluble KNO3 @ 0.5% at FI and PF stage; foliar spray of borate @ 0.5 % at FI stage; foliar spray of borate @ 0.5 % at FI and PF stage; foliar spray of micronutrient 6’S element (Fe, Zn, Mn, Cu, Mo, B) @ 0.5 % at FI stage and foliar spray of micronutrient 6’S element (Fe, Zn, Mn, and Cu, Mo, B) @ 0.5 % at FI and PF stage was laid out in randomized block design with replicated thrice. Results revealed that foliar application of micronutrient 6’s element (Fe, Zn, Mn, Cu, Mo, B) at 0.5 % concentration at flower initiation and pod formation stage exhibited the highest growth and yield attributes of mungbean viz., plant height at maturity (78.0 cm), number of branches per plant (8.2), number of active nodules at flowering (24.7), number of pods per plants (61.1), number of seeds per pods (13.2) and 1000-grain weight (42.7 gm) grain yield (1.32 t/ha). This treatment also resulted in significant improvement in net returns (₹81,566/ha), B:C ratio (2.6), production efficiency (19.4 kg/ha/day) and monetary efficiency (₹1199/ha/day).  However, the lowest value was observed without foliar application. It was concluded that foliar application of micronutrient 6’S element (Fe, Zn, Mn, and Cu, Mo, B) @ 0.5% at flower initiation and pod formation stages exhibited superior growth, yields and returns under the hot arid conditions of Rajasthan (India).